Carbon stock dynamics of forest to oil palm plantation conversion for ecosystem rehabilitation planning - D. Frianto; E. Sutrisno; A. Wahyudi; E. Novriyanti; W.C. Adinugroho; A.S. Yunianto; H. Kurniawan; H. Khotimah; A. Windyoningrum; I.W.S. Dharmawan; H.L. Tata; S. Suharti; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Efforts to enhance carbon stocks and boost carbon absorption potential are essential for climate change mitigation. Peatland ecosystems, known for their high organic content, are particularly vulnerable to environmental management. The study aimed to examine the alterations in land use and land cover that occurred between 1998 and 2022, spanning a 24-year duration. Additionally, it sought to assess the associated variations in carbon stocks within the designated Kepau Jaya specific purpose forest area. The area under investigation encompasses a peatland ecosystem that has experienced substantial changes in land cover and land use. This study investigated the fluctuations in carbon stock caused by these alterations and provides valuable perspectives on the potential of agroforestry systems to promote a wider range of land uses. Additionally, it highlights their role in ecosystem restoration initiatives and the better management of forest peatland regions.METHODS: A spatial analysis was conducted on Landsat 5 and 8 satellite images by using shapefile data stored within the Google Earth Engine platform. Data analysis was carried out using Classification and Regression Tree, a decision tree algorithm used in machine learning for guided classification. Furthermore, purposive sampling was utilized to gather socioeconomic data, followed by the implementation of a benefit-cost analysis.FINDINGS: The results revealed significant changes in the land cover within the Kepau Jaya specific purpose forest area over a 24-year period, with forested areas and open areas decreasing by 23.15 hectares per year and 16.94 hectares per year respectively, and oil palm plantation areas expanding by 40.10 hectares per year. From 1998 to 2022, there has been a consistent annual decline in carbon stocks, resulting in a reduction of 1,933.11 tons of carbon per year. The changes in land use and cover are closely linked to this decline. In an effort to increase plant species diversity in the area and support the gradual transition away from monoculture, a participatory agroforestry scheme was implemented by intercropping Coffea liberica and Shorea balangeran between oil palm rows in a 2-hectare oil palm plantation block within the agroforestry demonstration plot. According to measurements taken at breast height, the aboveground biomass of these species was measured, leading to projected estimates of carbon stocks in Kepau Jaya specific purpose forest area reaching 19,455 tonnes of carbon by the year 2030, with Coffea liberica contributing 4,148 tonnes carbon and Shorea balangeran contributing 15,307 tonnes carbon. CONCLUSION: The study area experienced a substantial reduction in forest cover, whereas the extent of oil palm areas expanded significantly. The findings underscore the need for proactive measures to strengthen the governance of specific-purpose forest areas through community empowerment and the establishment of demonstration plots to promote agroforestry development. The results of this study provide insights for long-term forest rehabilitation strategies aimed at fostering sustainable forest management that yields environmental and socio-economic benefits in the long run.